A rare and incidental finding during colonoscopy: solitary polypoid ganglioneuroma: A case report - Usturalı Keskin, Elif; Yılmaz, Tufan; Şen, Gürol (Journal of Surgery and Medicine, 2019)
Ganglioneuromas (GNs) are benign, slow growing and well differentiated neuroectodermal neoplasias. They are derived from developing neuronal cells of the sympathetic nervous system. They occur mostly in children and are located in the posterior mediastinum, retroperitoneum. We present a case of incidental solitary polypoid ganglioneuroma of the colon. A 70 year old woman underwent colonoscopy for colon cancer screening. She has no abdominal or intestinal symptoms. In hepatic flexure of the colon a spherical polypoid lesion that was 1.4 cm in diameter was detected endoscopically. Biopsy was taken from the polyp. The histopathology revealed a biphasic polypoid tumour with ganglion cells and schwannian stroma on hematoxylin and eosin stain. Final histopathological diagnosis was polypoid ganglioneuroma of the colon. Ganglioneuromatous polyposis and diffuse ganglioneuromatosis are associated with several systemic syndromes. Solitary GNs are generally asymptomatic. Treatment of GNs depends on their size, location, and clinical findings such as bleeding or obstruction. Prognosis is usually excellent. Polypectomy is curative for polypoid GN. However the patients with ganglioneuromatous polyposis and diffuse form may need colectomy.